2000
DOI: 10.1002/1096-9861(20000807)423:4<603::aid-cne6>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and development of nicotinic acetylcholine receptor subtypes in the optic tectum ofRana pipiens

Abstract: Acetylcholine allows the elicitation of visually evoked behaviors mediated by the frog optic tectum, but the mechanisms behind its effects are unknown. Although nicotinic acetylcholine receptors (nAChRs) exist in the tectum, their subtype has not been assessed. By using quantitative autoradiography, we examined the binding of [(3)H]cytisine and [(125)I]alpha-bungarotoxin in the laminated tectum. In mammalian systems, these radioligands bind with high affinity to alpha4 nAChR subunits and alpha7 nAChR subunits,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 93 publications
(176 reference statements)
2
23
0
Order By: Relevance
“…Nicotine activates two classes of receptors: α‐bungarotoxin‐sensitive and α‐bungarotoxin‐insensitive nicotinic receptors. Both of these receptor classes are present in the optic tectum (Butt et al ., 2000). To determine which nicotinic receptor subtype mediated nicotine‐induced map refinement, we chronically exposed the tectum to either anatoxin‐a, an agonist selective for α‐bungarotoxin‐sensitive nicotinic receptors, or epiboxidine, an agonist selective for nicotinic receptors that are insensitive to α‐bungarotoxin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nicotine activates two classes of receptors: α‐bungarotoxin‐sensitive and α‐bungarotoxin‐insensitive nicotinic receptors. Both of these receptor classes are present in the optic tectum (Butt et al ., 2000). To determine which nicotinic receptor subtype mediated nicotine‐induced map refinement, we chronically exposed the tectum to either anatoxin‐a, an agonist selective for α‐bungarotoxin‐sensitive nicotinic receptors, or epiboxidine, an agonist selective for nicotinic receptors that are insensitive to α‐bungarotoxin.…”
Section: Resultsmentioning
confidence: 99%
“…Both α‐bungarotoxin‐sensitive and ‐insensitive receptors are present in the frog optic tectum (Butt et al ., 2000). Through the use of subtype‐selective agonists, we have shown that map refinement can be achieved through either nicotinic receptor subtype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disruption of retinal inputs reduces nAChR ␣5, ␤2, and ␣7 subunit protein levels in the chick optic tectum neuropil (Britto et al, 1994;Torrao et al, 1996), and decreases binding of the nAChR ligands ␣-bgt and cytosine in the frog tectum (Sargent et al, 1989;Butt et al, 2000). These studies are complicated by the fact that nAChRs are expressed on both innervating presynaptic terminals and postsynaptic neurons found in the tectal neuropil, raising the possibility that degeneration of the lesioned nerve contributes to the loss of nAChR expression following denervation (Sargent et al, 1989;Torrao et al, 1996;Butt et al, 2000;Britto et al, 2001). Nonetheless, continued expression of nAChRs in mature CNS neurons appears to require regulatory signals from presynaptic afferents, just as in the PNS.…”
Section: Maintenance Of Nachr Expression Requires Innervationmentioning
confidence: 99%
“…The optic tectum of the frog contains both nicotinic and muscarinic cholinergic receptors (Sargent et al, 1989;Birdsall et al, 1980;Butt et al, 2000Butt et al, , 2001) but knowledge of the physiological consequences of their activation is incomplete. Assessments of the effects of nicotinic receptor activation have focused on a facilitation of glutamate release from retinal ganglion cell terminals (Titmus et al, 1999;Kuras and Gutmaniene, 2001) while muscarinic receptors have been associated with tectal cell membranes following an enhancement of single unit recordings in response to ACh microiontophoresis (Fite and Wang, 1986).…”
mentioning
confidence: 99%